Decree 9.283/2018 from the perspective of creating strategic alliances (Research, Society and Development, 2020)
The Technological Innovation Law under number 10,973 of December 2, 2004, was enacted in order to promote measures to encourage innovation and scientific and technological research in the productive environment, and thus achieve the country's economic development. However, research carried out in universities, despite having acquired a crucial role in the field of knowledge and the development of new technologies, its application in the market is still incipient. Thus, Decree 9.283/2018 regulates Law 10.973, in addition to others, whose purpose is the achievement of technological autonomy and the development of the national and regional productive system. Based on these assumptions, the article aims to analyze Law 9.283 / 2018 and understand the connections between the company and the university, from the point of view of the perception of the creation of strategic alliances. The research has a qualitative exploratory character, in which an analysis of Decree 9.283 / 2018 was made under the perspective of creating strategic alliances that allow cooperation between university and company, as a way of developing new technologies that can be commercialized. In methodological terms, secondary data were collected using the Form for Information on the Intellectual Property Policy of Scientific, Technological and Innovation Institutions in Brazil (FORMICT), available at the Ministry of Education's website www.mctic.gov.br Science, Technology, Innovations and Communications (MCTIC). Thus, presenting a proposal for a simplified conceptual model of strategic alliances for Science and Technology Institutions.